How to prepare data for the automatic classification of politically related beliefs expressed on Twitter? The consequences of researchers’ decisions on the number of coders, the algorithm learning procedure, and the pre-processing steps on the performance of supervised models - Matuszewski, Paweł (Quality & quantity, 2023)
Due to the recent advances in natural language processing, social scientists use automatic text classification methods more and more frequently. The article raises the question about how researchers’ subjective decisions affect the performance of supervised deep learning models. The aim is to deliver practical advice for researchers concerning: (1) whether it is more efficient to monitor coders’ work to ensure a high quality training dataset or have every document coded once and obtain a larger dataset instead; (2) whether lemmatisation improves model performance; (3) if it is better to apply passive learning or active learning approaches; and (4) if the answers are dependent on the models’ classification tasks. The models were trained to detect if a tweet is about current affairs or political issues, the tweet’s subject matter and the tweet author’s stance on this. The study uses a sample of 200,000 manually coded tweets published by Polish political opinion leaders in 2019. The consequences of decisions under different conditions were checked by simulating 52,800 results using the fastText algorithm (DV: F1-score). Linear regression analysis suggests that the researchers’ choices not only strongly affect model performance but may also lead, in the worst-case scenario, to a waste of funds.